Influence of drought stress on phosphorus dynamics and maize growth in tropical ecosystems - Mohsin Mahmood; Jujie Wang; Sajid Mehmood; Waqas Ahmed; Anam Ayyoub; Mahmoud F. Seleiman; Ahmed Salah Elrys; Ahmed S. M. Elnahal; Adnan Mustafa; Xiuwen Wei; Weidong Li (BMC Plant Biology)
Abstract Drought has a significant impact on ecosystem functions, especially on the biogeochemical cycling of phosphorus (P), which is a crucial nutrient for plant growth and productivity. Despite its importance, the effects of different drought scenarios on soil P cycling and availability remain poorly understood in previous studies. This study simulated drought conditions in tropical soils using maize as a test crop under varying field capacity (FC) levels (100%, 80%, 60%, 40%, and 20%) over a 60-day pot experiment. P uptake and plant biomass decreased significantly lower FC level. P uptake was highest at FC100 (5 g kg−¹) and lowest at FC20 (3.5 g kg−¹). Similarly, biomass was greatest at FC100 (70 g plant−¹) and declined to 35 g plant−¹ at FC20, underscoring the adverse effects of drought on P availability and growth. The results showed a substantial increase in calcium-associated P (HClD-Pi), reaching 45% at FC20. Conversely, labile inorganic P fractions (NaHCO₃-Pi and NaOH-Pi) decreased significantly, from 14.73 to 6.2 mg kg−¹ and 29.4 to 17.7 mg kg−¹, respectively, in FC20 compared to FC100. Organic P fractions (NaHCO₃-Po, NaOH-Po) increased by 6 and 2.4 times, respectively, under lower FC treatments, while HClc-Po was also elevated under drier conditions. These transformations were attributed to changes in soil pH and calcium content, favoring the stabilization of P as HClD-Pi. Drought disrupted the replenishment of inorganic P in the soil solution, reducing bioavailability, though phosphatase activity enhanced organic P release. Pearson’s correlation analysis revealed positive associations between labile and moderately labile P fractions (NaHCO₃-Pi, NaOH-Pi, HClD-Pi) and soil elements (Ca, Al, Fe). RDA highlighted a positive link between phosphatase activity and reduced labile P, while P uptake and biomass were strongly associated with labile and moderately labile P fractions. These findings demonstrate drought’s significant impact on P bioavailability, soil P cycling, and nutrient dynamics.